(untitled) (The Pakistan Development Review, 2006)
The paper explores the linkages between poverty, growth and inequality in the context of Pakistan. Time series macro data are used for the period 1979 to 2002. Consistent poverty and inequality measures are interpolated to facilitate the estimation of poverty elasticity with respect to growth and inequality in a multivariate regression framework. The paper also attempts to find out macroeconomic and structural correlates of inequality. The empirical findings—high poverty elasticity with respect to inequality measures—confirm the importance of inequality in poverty reducing effort. Inflation, sectoral wage gap, and terms of trade in favour of manufacturing exacerbate inequality, while progressive taxation, investment and development expenditure on social services play a significant role in reducing inequality. The results also indicate a positive correlation between per capita GDP and income inequality.